Experimental and Applied Immunotherapy - Medin, Jeffrey; Fowler, Daniel; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Immunotherapy is now recognized as an essential component of treatment for a wide variety of cancers. It is an interdisciplinary field that is critically dependent upon an improved understanding of a vast network of cross-regulatory cellular populations and a diversity of molecular effectors; it is a leading example of translational medicine with a favorable concept-to-clinical-trial timeframe of just a few years. There are many established immunotherapies already in existence, but there are exciting new cancer immunotherapies just on the horizon, which are likely to be more potent, less toxic and more cost effective than many therapies currently in use. Experimental and Applied Immunotherapy is a state-of-the-art text offering a roadmap leading to the creation of these future cancer-fighting immunotherapies. It includes essays by leading researchers that cover a wide variety of topics including T cell and non-T cell therapy, monoclonal antibody therapy, dendritic cell-based cancer vaccines, mesenchymal stromal cells, negative regulators in cancer immunology and immunotherapy, non-cellular aspects of cancer immunotherapy, the combining of cancer vaccines with conventional therapies, the combining of oncolytic viruses with cancer immunotherapy, transplantation, and more. The field of immunotherapy holds great promise that will soon come to fruition if creative investigators can bridge seemingly disparate disciplines, such as T cell therapy, gene therapy, and transplantation therapy. This text is a vital tool in the building of that bridge.
Foreword, by Carl H. June, M.D. -- Chapter 1: Extending the Use of Adoptive T Cell Immunotherapy for Infections and Cancer -- Chapter 2: B Lymphocytes in Cancer Immunology -- Chapter 3: Monoclonal Antibody Therapy for Cancer -- Chapter 4: Natural Killer Cells for Cancer Immunotherapy -- Chapter 5: Dendritic Cell Based Cancer Vaccines: Practical Considerations, by Elizabeth Scheid, Michael Ricci -- Chapter 6: Mesenchymal Stromal Cells: an Emerging Cell-based Pharmaceutical -- Chapter 7: Tumor-specific Mutations as Targets for Cancer Immunotherapy -- Chapter 8: Counteracting Subversion of MHC Class II Antigen Presentation by Tumors -- Chapter 9: Mechanisms and Implications of Immunodominance in CD8+ T-Cell Responses -- Chapter 10: T Regulatory Cells and Cancer Immunotherapy -- Chapter 11: Negative Regulators in Cancer Immunology and Immunotherapy -- Chapter 12: Genetically Engineered Antigen Specificity in T Cells for Adoptive Immunotherapy -- Chapter 13: Cytokine Immunotherapy -- Chapter 14: Transcriptional Modulation using Histone Deacetylase Inhibitors for Cancer Immunotherapy -- Chapter 15: Combining Cancer Vaccines with Conventional Therapies -- Chapter 16: Combining Oncolytic Viruses with Cancer Immunotherapy -- Chapter 17: XRT and Immune Therapy -- Chapter 18: Assessing Immunotherapy through Cellular and Molecular Imaging -- Chapter 19: Converging Themes in Allogeneic and Autologous Transplantation.
Keywords: Immunology; Cell biology; Immunology; Cell Biology